2022
DOI: 10.1186/s41065-021-00216-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four novel hub genes as monitoring biomarkers for colorectal cancer

Abstract: Background It must be admitted that the incidence of colorectal cancer (CRC) was on the rise all over the world, but the related treatment had not caught up. Further research on the underlying pathogenesis of CRC was conducive to improving the survival status of current CRC patients. Methods Differentially expressed genes (DEGs) screening were conducted based on “limma” and “RobustRankAggreg” package of R software. Weighted gene co-expression netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…TMIGD1 is a cell adhesion receptor that has drawn attention after the discovery that its expression is progressively downregulated during the development of colorectal cancer in humans [ 16 ]. Meanwhile, a number of studies have confirmed a highly significant downregulation not only in colorectal cancer but also in renal cancer, strongly supporting a tumor-suppressive function of TMIGD1 and suggesting that TMIGD1 expression may be used as a prognostic marker [ 19 , 63 , 69 ]. Also, the molecular biology underlying its functions is beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TMIGD1 is a cell adhesion receptor that has drawn attention after the discovery that its expression is progressively downregulated during the development of colorectal cancer in humans [ 16 ]. Meanwhile, a number of studies have confirmed a highly significant downregulation not only in colorectal cancer but also in renal cancer, strongly supporting a tumor-suppressive function of TMIGD1 and suggesting that TMIGD1 expression may be used as a prognostic marker [ 19 , 63 , 69 ]. Also, the molecular biology underlying its functions is beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…A RNAseq-based comparison of hyperplastic polyp lesions with colorectal adenoma lesions identified TMIGD1 among the top 10 down-regulated genes in colorectal adenoma [ 68 ], confirming a gradual downregulation of TMIGD1 expression during the development of colon cancer. Another analysis using CRC-derived microarrays that were based on 369 carcinoma samples from 9 different datasets of different geographical origin identified TMIGD1 as one among 22 hub genes whose downregulation in CRC samples was most significant [ 69 ]. Additional observations describing reduced TMIGD1 expression in CRC samples were made in studies comparing colonic non-adenomatous, non-neoplastic tissue with colonic tumor tissue, with TMIGD1 being among the 11 most significantly downregulated genes in colonic tumor tisse [ 70 ].…”
Section: Tmigd1 Expression In Cancer and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…A role of TMIGD1 in recruiting Scrib to the lateral membrane is consistent with a predicted function of TMIGD1 as tumor suppressor protein. Several unbiased studies describe a strong and highly significant reduction of TMIGD1 gene expression in colon cancer in humans 72 75 with a progressive downregulation during disease progression 21 , 76 . Also, several studies found a significant downregulation of TMIGD1 gene expression in diseases associated with chronic intestinal inflammation such as Crohn’s disease or inflammatory bowel disease 26 , 73 , 77 , conditions which promote carcinogenesis 78 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the articles utilize web-based tools for validation. For instance, Luo D et al, 2022 used the MEXPRESS web-based tool to visualize the relationship between gene expression and methylation extend in hub genes related to Colorectal cancer [115] . Tong Lin et al, 2021 employed DNMIVD, SurvivalMeth, and MethServ tools for estimating the correlation between the expression level and the methylation density of DEGs, estimating the global methylation, and finding an association between the methylation level of CpG sites of the DEGs and overall survival of hepatocellular carcinoma patients, respectively [116] .…”
Section: Dna Methylation Microarray Data Analysismentioning
confidence: 99%